Life Span Development - W.Santrock John (McGraw -Hill, 2005)
This best-selling, learning style-focused textbook is designed for the chronologically organized human development course. It is widely adopted for being the most accurate and up to date text available. Included in this new edition are the largest number of 21st century citations of any text on the market, a streamlined chapter organization and Learning Goals-driven learning system, and thoroughly integrated coverage of culture, ethnicity, and gender. --This text refers to an out of print or unavailable edition of this title.